Resposta :
ExplicaĆ§Ć£o passo-a-passo:
1) 3Ā².2ā“+1 =
9.16+1=
144+1=
145
2) 5Ā².3-6Ā²:2 =
25.3-36:2=
75-18=
57
3) 5.2Ā³+7Ā² =
5.8+49=
40+49=
89
4) 7ā°+6ā°-(7+6)ā° =
1+1-(13)^0=
2-1=
1
5) 2ā“.3.5.+3Ā² =
16.3.5.9=
48.45=
2160
6) 2.4Ā³+8Ā²+2āµ =
2.64+64+32=
128+96=
224
7) 17-3.2Ā²+2āµ =
17-3.4+32=
17-12+32=
5+32=
37
8) 10ā°+2.10Ā²-10.2Ā³ =
1+2.100-10.8=
1+200-80=
1+120=
121
9)1ā°+1Ā¹+2ā°+2Ā¹+2Ā² =
1+1+1+2+4=
2+3+4=
5+4
9
10) 2Ā².3+8:2-ā36 =
4.3+4-6=
12+4-6=
16-6=
10
11) 20-ā4+3Ā².3-2:2 =
20-2+9.3-1=
20-2+27-1=
18+26=
44
12) 2.(3Ā²-3.2)ā“+(3.3Ā²+1)Ā² =
2.(9-6)^4+(3.9+1)^2=
2.(3)^4+(27+1)^2=
2.81+(28)^2=
2.81+784=
162+784=
946
13) (3.2Ā³-2.3Ā²)Ā³:(2Ā².3) =
(3.8-2.9)^3:(4.3)=
(24-18)^3:(12)=
(6)^3:(12)=
216:(12)=
18
14) [(10-ā25)Ā²-(3+2Ā³+4)]Ā² =
[(10-5)^2-(3+8+4)]^2=
[(5)^2-(11+4)]^2=
[25-(15)]^2=
[10]^2=
20
15) 10Ā²-ā12+4.3Ā¹+3Ā¹:ā10-1 =
100-3,46+4.3+3:3,16-1=
100-3,46+12+0,94-1=
96,54+12,94-1=
109,48-1=
108,48
16) (2āµ-2ā“-2Ā³-2Ā²).(1+1Ā²+1Ā³) =
(32-16-8-4).(1+1+1)=
(16-4).(2+1)=
(12).(3)=
36
17) 12.(ā25+ā49+ā144+ā1)āµ =
12.(5+7+12+1)^5=
12.(12+13)^5=
12.(25)^5=
12.9765625=
117187500
18) {2āµ-[2ā“-(2Ā³-2Ā¹)]}.(1+2Ā²+1Ā³) =
{32-[16-(8-2)]}.(1+4+1)=
{32-[16-(6)]}.(5+1)=
{32-[10]}.(6)=
{22}.(6)=
132
19) 32:2ā“+(11-3Ā²).(4Ā³-3Ā³) =
32:16+(11-9).(64-27)=
32:16+(2).(37)=
2+74=
76
20) (10-2Ā³).3Ā²+5Ā².[2ā“-(4Ā³-7Ā²)]=
(10-8).9+25.[16-(64-49)]=
(2).9+25.[16-(15)]=
(2).9+25.[1]=
18+25=
43
Espero ter ajudado ā¤.